2008
DOI: 10.1590/s0102-695x2008000500026
|View full text |Cite
|
Sign up to set email alerts
|

Plants with anticonvulsant properties: a review

Abstract: RESUMO: "Uma revisão de plantas com propriedades anticonvulsivantes". Cerca de um terço dos pacientes epilépticos não conseguem ter um tratamento adequado com as drogas anticonvulsivantes atuais. Nesse sentido, as plantas medicinais surgem como uma fonte promissora de novas moléculas químicas com propriedades biológicas apreciáveis. Muitas plantas ou produtos de origem naturais têm sido propostos para o tratamento de várias patologias, tais como: epilepsia, diabetes, ansiedade, depressão, dentre outras. O pres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
43
0
14

Year Published

2009
2009
2018
2018

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 108 publications
(58 citation statements)
references
References 150 publications
0
43
0
14
Order By: Relevance
“…Several Ocimum species (Lamiaceae) are used to treat central nervous system (CNS) disorders in various parts of the world and its anticonvulsant activity is frequently reported (Quintans-Júnior et al, 2008b;Oliveira et al, 2009). Ocimum basilicum L. essential oil is rich in monoterpenes, such as δ-cadinol (10.2%), estragole (22.6%), and linalool (47.3%) (Mazutti et al, 2006 (Blank et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Several Ocimum species (Lamiaceae) are used to treat central nervous system (CNS) disorders in various parts of the world and its anticonvulsant activity is frequently reported (Quintans-Júnior et al, 2008b;Oliveira et al, 2009). Ocimum basilicum L. essential oil is rich in monoterpenes, such as δ-cadinol (10.2%), estragole (22.6%), and linalool (47.3%) (Mazutti et al, 2006 (Blank et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…An increasing number of studies have demonstrated that essential oils derived from plants exhibit a variety of biological properties, such as anticonvulsant (Quintans-Júnior et al, 2008a), analgesic and Central Nervous System (CNS) activities (Carlini, 2003;Silva et al, 2007). Monoterpenes are the primary components of essential oils and the effects of many herbal medicines have been attributed to them (Gherlardini et al, 2001;De Sousa et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…However, the efficacy and trustworthiness in medicinal plant products have demonstrated the real value of these materials. Brazil have a great diversity of native plants (Mors, et al, 2000, Barbosa-Filho, et al, 2005, Brandão, et al, 2006Quintans-Júnior et al, 2008), but its medicinal properties had had not been adequately studied yet. The scientific study of plants used in folk medicine is essential to lower the adverse effect risk for populations (Agra et al, 2008).…”
Section: Introductionmentioning
confidence: 99%